The genus Hyperphyscia Müll.Arg. (Physciaceae, Ascomycota) in Argentina - Filippini, Edith Raquel (2015)
A total of 13 species of genus Hyperphyscia were identified. A description is given for each species, including ecology and distribution data. The taxonomic status of each species is discussed. Hyperphyscia confusa, H. pyrithrocardia and H. minor are new records from Argentina. Hyperphyscia cochlearis is synonymous with H. variabilis. The new combination Hyperphyscia endochrysea is proposed.